MENYIKAPI MUSIBAH DALAM PANDANGAN ISLAM - Asad Asad (Universitas Islam Negeri Sumatera Utara Medan, 2021)
Disaster has not stopped by human in the world in general and Indonesia especially, such as the corona virus (Covid-19), earthquakes, landslides, flash floods, tsunami 2004, are still fresh in our memories, even at the beginning In 2021, all elements of the nation felt deep sorrow for the incident of the crash of the Sriwijaya Air plane with flight number SJ 182 to Jakarta - Pontianak which killed 60 passengers and crew of the Sriwijaya Air plane, and many other calamities that the author could not mention one by one, including Israeli atrocities against Palestinians.Keyword: Menyikapi Musibah, Pandangan, dan Islam.